2012
DOI: 10.4161/cc.20718
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and senescence in cancer-associated fibroblasts metabolically supports tumor growth and metastasis, via glycolysis and ketone production

Abstract: Senescent fibroblasts are known to promote tumor growth. However, the exact mechanism remains largely unknown. An important clue comes from recent studies linking autophagy with the onset of senescence. Thus, autophagy and senescence may be part of the same physiological process, known as the autophagy-senescence transition (AST). To test this hypothesis, human fibroblasts immortalized with telomerase (hTERT-BJ1) were stably transfected with autophagy genes (BNIP3, CTSB or ATG16L1). Their overexpression was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 82 publications
9
173
0
2
Order By: Relevance
“…Conclusively, the investigators stated that autophagia was effective in tumor growth independent of angiogenesis. 27 It was observed that CTSB expression was increased in tumor tissues compared to normal tissues in our cases in accordance with the literature.…”
supporting
confidence: 81%
“…Conclusively, the investigators stated that autophagia was effective in tumor growth independent of angiogenesis. 27 It was observed that CTSB expression was increased in tumor tissues compared to normal tissues in our cases in accordance with the literature.…”
supporting
confidence: 81%
“…46 Similarly, genetic induction of ketone body production in cancer-associated fibroblasts (by expression of ATG16L1 or HMGCS2, or via silencing of the BRCA1 gene) promotes both tumor growth and/or metastasis. 27,32,47 Finally, genetic induction of mitochondrial biogenesis in cancer cells (by expression of PGC1-α/β; POLRMT; or MitoNEET) promotes tumorigenesis. 48 Thus, we have identified (1) stromal ketone production and (2) mitochondrial biogenesis in epithelial cancer cells as two key metabolic components which are energetically driving tumor cell growth and cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also validate the "two-compartment tumor metabolism" model of tumorigenesis. 21,[27][28][29][30][31][32][33][34] …”
Section: Mitochondrial Dysfunction In Breast Cancer Cells Prevents Tumentioning
confidence: 99%
“…In direct support of this hypothesis, genetic induction of mitochondrial dysfunction in cancer-associated fibroblasts dramatically promotes both local tumor growth and distant cancer cell metastasis. [12][13][14][15][16][17][18][19][20][21][22][23][24] Conversely, genetic amplification of mitochondrial biogenesis in epithelial cancer cells also promotes tumor growth, independently of neo-angiogenesis. 23,[25][26][27][28] Consistent with these pre-clinical findings, we have identified a series of new stromal biomarkers and related gene signatures that are characteristic of this type of lethal cancer metabolism.…”
Section: Introductionmentioning
confidence: 99%